Analisis Faktor-Faktor Yang Berpengaruh Terhadap Profitabilitas Perbankan Yang Go Public di Bursa Efek Indonesia Periode 2020-2024 (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to analyze the factors that affect the profitability of banks that go public on the Indonesia stock exchange for the period 2020-2024. The population of this study were 57 banks listed on the Indonesia Stock Exchange and the total sample collected from the purposive sampling method was 10 banks for the 2020-2024 period, obtaining 50 observation data. The data used is secondary data in the form of financial statements with the analysis carried out including inferential statistics, classical assumption tests, panel data regression tests and hypothesis tests (t test, F test, coefficient of determination) which are analyzed using the Eviews version 12 application. The results of the research conducted explain that the Capital Adequacy Ratio (CAR), Net Interest Margin (NIM) has no partial effect on Return On Asset (ROA), while Operating Costs and Operating Income (BOPO) and Net Performing Loan (NPL) have a partial effect on Return On Asset (ROA). The F test results explain that the Capital Adequacy Ratio (CAR), Operating Costs and Operating Income (BOPO), Net Performing Loan (NPL), and Net Interest Margin (NIM) simultaneously affect Return On Asset (ROA).